PENGARUH PEMAHAMAN PERATURAN PERPAJAKAN, KESADARAN WAJIB PAJAK, DAN PERSEPSI TENTANG SANKSI PA-JAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI (STUDI PADA WPOP DI MASPION SQUARE SURABAYA) - Michael, Michael; Rahardjo, Hartono; Irawan, Ronny (Jurnal Akuntansi Kontemporer, 2013)
Tax is source of funding in the country, which are crucial in Indonesia. Tax System in Indonesia using the self-assessment system requires taxpayers to calculate, pay, and report himself to the KPP. This system requires taxpayers independence that can affect the level of tax compliance. There are several factors that affect tax compliance, ie the understanding of tax laws, taxpayer awareness and perception of tax penalties. These variables are used as in previous studies tended to correspond to individual tax-payers. Therefore, this study examined the influence of understanding tax laws, taxpayer awareness and perceptions of sanctions levied on individual tax compliance. This study used a questionnaire as tool of collecting data. Object of this study is a taxpayer conducting trading business in Maspion Square Surabaya. A total of 66 questionnaires that have been distributed, and only 54 questionnaires that can be pro-cessed and carried out the research. The results of this study are jointly variable understanding of tax laws, taxpayer awareness and perceptions of sanctions taxes affect individual tax compliance, but based on the T-test statistic that understanding the tax laws resulting positive effect on tax compliance of taxpayers and consciousness person and perceptions of tax penalties is not a positive influence on individual tax compliance.